Fifty Years of U.S. Natural Disaster Insurance Policy - Kendra Marcoux; Katherine R. H. Wagner (Center for Economic Studies and ifo Institute (CESifo), 2023)
The high and increasing cost of natural disasters around the world motivates a growing body of literature on the role of natural disaster insurance in adapting to climate change. This chapter reviews current challenges in both public and private natural disaster insurance markets in the United States and how the nature of these challenges has changed over the past fifty years. We discuss how the infrequent, spatially correlated, and extreme events that distinguish these markets complicate both the supply of and demand for natural disaster insurance, with spillovers to related markets such as real estate. We also highlight open questions that would be helpful to answer to inform analysis of currently proposed natural disaster insurance reforms.
Keywords: H53; H84; Q54; 330; natural disaster insurance; climate change; adaptation